An Evaluation of Students' Industrial Training Programs in the Hospitality Industry: A Case Study of Three Public Universities in Ashanti Region, Ghana - Commey, Vida; Amoako Sarkodie, Noble; Impraim, Evelyn Catherine (Journal of Tourism and Hospitality Studies, 2023)
Industrial attachment is regarded as one of the most relevant aspects of the academic curriculum of tertiary institutions across the globe. Industrial attachment offers students the opportunity to prepare themselves for the job market by gaining relevant insight into what pertains to the world of work. This study aims to investigate the perception of students on the effectiveness of industrial training in academic programmes offered at three Universities in Kumasi, the Ashanti region of Ghana. This study utilized a case study research design and quantitative research approach to solicit from 284 students from the departments of Tourism and Hospitality in the three universities who had undergone practical industrial training in their previous semesters through close ended questionnaires. The study employed descriptive statistics and linear regression analysis to analyse the data collected. The findings of the study revealed that the perception of students on the effectiveness of industrial training was generally positive, with an average ranking score of ±89.62%. The study established that the major factor that had a positive influence on the perception of the students on the effectiveness of their previous industrial training programme was the host company’s support. It was, however, observed that the majority of the students (89%) lacked pre-placement orientation, while another 85% also lacked departmental support during their industrial training programme. The study recommends that students should be given the proper orientation before their placement to give them insight into what to expect while on their internship. The departments in the university should also create a feedback system that will allow them to supervise, monitor and also follow-up on the progress of their students while on industrial training programmes.